Investigation of the influence of flow rate on bubble formation and collapse in ball values at various opening percentages using an AE technique - Alhashan, Taihiret; Addali, Abdulmajid; Teixeira, Joao Amaral (The British Institute of Non-Destructive Testing, 2018)
Ball valves are popularly used in many different industrial processes and hydraulic systems because of their light weight and simple structure. However, they are susceptible to cavitation phenomena and the growth and collapse of the bubbles formed lead to erosion and pitting of the metal surfaces. This paper presents the monitoring and detection of bubble formation at an early stage in a ball valve using acoustic emission (AE). It is shown that AE will detect incipient cavitation and that there is a clear correlation between AE signal level and the flow rate through the ball valve at a constant opening percentage.
Keywords: Acoustic emission; Ball value; Bubble formation; Cavitation; Monitoring